An Analysis on HOTS of Reading Exercises in English Textbook - Indri Fitriani; Susilawati Susilawati; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2021)
As one of the learning sources, textbooks play an important role in English teaching and learning process to facilitate students in knowing and obtaining teaching materials easily. Currently, the Ministry of Education and Culture of Indonesian revised the 2013 curriculum which is students are required to think deeply to develop their cognitive competence and to emphasize their critical thinking. The purpose of this study is to get a distribution of the Higher-order thinking skills on KTSP textbook that is still used as a reference many schools the book’s title is Developing English Competencies for grade X. The study focuses on analysing the questions using question word based on the revised Bloom’s Taxonomy. The researcher used content analysis research design. Moreover, the researcher used indicator references of cognitive higher-order thinking skills in the language classroom and the table checklist used. The result of the distribution on HOTS and LOTS are as follow. There are 7 questions from 64 questions word or 10,9% (HOTS) there are 57 questions from 64 question word or 89,1% (LOTS). Hence, the distribution of HOTS reading exercises is lower than the distribution of LOTS reading exercises in Developing English Competencies Textbook. Keywords: English textbook; HOTS (Higher Order Thinking Skill); Bloom’s Taxonomy